Impact of social media on e-tourism : a critical analysis of determinants of decision making / V. Sivakumar. - Sivakumar, V.; Saranya, PR.; Leelapriyadharsini, S.; Iyappan, A. (Universiti Teknologi Mara Selangor, 2019)
E-Tourism is an emerging trend among the other e-commerce market. Availability of online tourism services has transformed the traditional approach of people in planning their tours and it engage nearly three-fourth of e-commerce share in India. Social media has boomed as the new mode to connect people thus leveraging the impact of social media platform to promote tourism products has established to be an excellent strategy. Social networking sites such as blogs, micro blogs, consumer review sites, content community sites with maximum number of hits, wikis, internet forums and location based social media enable the users to communicate in a way to achieve information search, decision-making and also used by the service providers to achieve promoting tourism services. Exploratory research on the impact of social media in tourism is still in infancy. This paper reports on an online research to establish the various determinants of decision making on using social media for availing tourism services. Research tool is developed based on the extensive review of literature and an online survey is made among the users of relevant social media sites. The data is collected and quantitatively analysed to derive significant factors affecting the decision making of tourists. The authors would also like to acknowledge the funding under RUSA 2.0 Scheme of MHRD, Govt of India.